ANALISIS VEGETASI POHON DAN SERAPAN CO2 DI JALUR HIJAU KOTA PEKANBARU UNTUK PENGEMBANGAN MODUL KONSEP UPAYA PENANGGULANGAN PENCEMARAN UDARA PADA MATA PELAJARAN BIOLOGI DI SMA KELAS X - Shara Aljogja Sandra; Sri Wulandari; Nursal ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: Aims of this research is determine the vegetation of trees and CO2 uptake in Pekanbaru City Green Belt and to develop module concept of air pollution control efforts on biology content in senior high school grade X in November 2015 to January 2016. The method used is purposive sampling method at 23 locations of green belt, while the module development is done using ADDIE models. Parameters used include tree vegetation, crown cover and CO2 uptake. Tree vegetation in the Green Belt Pekanbaru City has 21 family, 49 species and 11.588 trees. Green Belt Pekanbaru City had a density of 416.040 trees/ha, the frequency of 5.266, the dominance of 165.711 m2/ha, the diversity index 1,404 (medium category). The kind that has the highest important value index is Swietenia macrophyla amounted to 94.468%. Crown cover obtained for 10.098 ha, while the CO2 uptake of 354.682 tons/ha. The results of the research can be developed in to a module by showing a very valid category (4.24) and the limited test results by leaners show good category (83.96).Key Words: Green belt, module, CO2 uptake, tree vegetation